ANALISIS BREAK EVEN TERHADAP PENJUALAN SEWA VILLA - Made Tania Arry Paramitha; Gusti Ayu Mahanavami; Wiryawan Suputra Gumi (JUIMA : JURNAL ILMU MANAJEMEN, 2018)
Break Even analysis is one way to set sales planning to achieve the desired profit. Villa Kubu Manggala Seminyak must reach the minimum rental villa rental rate so that at the time of budget preparation, the management knows the information of some minimum sales of the company. The purpose of this research is to calculate the amount of villa rental service minimum that must be reached villa so as not to suffer loss or reach break even. The types of data used in this study are: quantitative and qualitative data, with secondary data sources. Methods of data collection were done by interview and observation while the analysis technique used were: cost grouping, fixed cost allocation and variable cost, contribution margin and break even rate calculation.From the results of research and recapitulation results, the largest profit is obtained if the rental price of Two Bed Room villa type increased and followed by the lowest break-even level. From the results of the calculation of break-even analysis in 2016, it can be seen that the break event for 2016 was achieved when the sales volume reached Rp. 1,259,493,670 or as many as 712 villa units for a year. To reach the break even level Villa Kubu Manggala Seminyak should maintain the existing situation and keep trying to spend cost effectively and efficiently.